The influence of combined exposure to noise and whole-body vibration on hearing loss under simulated heavy equipment driving conditions. (August 2021) - Mohammad Javad Golhosseini, Seyyed; Aliabadi, Mohsen; Golmohammadi, Rostam; Farhadian, Maryam; Akbari, Mehdi; Hamidi Nahrani, Morteza; Samavati, Mehdi
Abstract: Noise-induced hearing loss (NIHL) is a serious problem in occupational environments; however, there is little information about hearing loss due to combined exposure to noise and vibration. This study aimed to investigate the combined effects of exposure to noise and whole-body vibration (WBV) on hearing responses under simulated heavy equipment driving conditions. A repeated measures study was designed to evaluate the changes in distortion product otoacoustic emissions (DPOAE) amplitudes as hearing responses to 40 min of noise and/or WBV exposure. Thirty healthy males with an average age of 30.17 (±3.94) years, exposed to noise level of 85 dB(A) and two WBV levels (0.87 and 1.3 m/s 2 ) in six experimental scenarios. The findings revealed that there was a significant change in DPOAE amplitudes after single noise exposure and combined noise and WBV exposure (p < 0.05); however, there was no significant difference in WBV exposure alone (p > 0.05). The changes in DPOAE amplitudes were greater in combined exposure to noise and WBV (1.3 m/s 2 ) in all sessions. The statistical analysis showed the effect sizes of the combined exposure to noise and WBV were more than the sum of the exposure to each one alone. It can be concluded that some synergic effects can occur in DPOAE amplitudes in the combined noise and WBV exposure under heavy equipment driving conditions. These findings can help the occupational health experts adapt the existing physical agents' exposure limits to the realistic conditions of the occupational settings.